IL-33 and Soluble ST2 Are Associated With Recurrent Spontaneous Abortion in Early Pregnancy - Zhao, Long; Fu, Jinhua; Ding, Feng; Liu, Juan; Li, Lin; Song, Qi; Fu, Yinghui (Frontiers in Physiology, 2022)
Objective: Normal pregnancy is related to the successful transition from type 1 cellular immunity to type 2 cellular immunity. Therefore, this study aimed to investigate whether there is abnormal expression of cytokines in the process of inducing Recurrent spontaneous abortion (RSA). Interleukin (IL)-33 is a new member of the IL-1 family, and ST2, as IL-33’s receptor, induced the production of type 2 cytokines. Methods: In this study, blood samples were collected from 19 non-pregnant women of normal childbearing age, 28 normal pregnant women, and 33 women with RSA. The serum concentrations of IL-33 and ST2 were detected by flow cytometry. Results: showed that the serum concentrations of IL-33 and ST2 in the RSA group were significantly higher than those in the healthy control group (IL-33: p<0.05; ST2: p<0.0001), and IL-33 and ST2 had a higher level in the process of RSA predictive value. In addition, this study initially found that the serum concentrations of IL-33 and ST2 were not significantly correlated with the number of weeks of pregnancy, and there was a lower correlation between IL-33 and ST2 during RSA. This result may be related to the small number of cases. Conclusion: This study is the first time to correlate the changes in serum concentrations of IL-33 and ST2 with RSA, which may be a novel biomarker for the prediction and treatment of RSA.